BUDAYA MALU PADA MASYARAKAT TENGGER DAN PENGARUHNYA TERHADAP BUDAYA HUKUM PENGHINDARAN KONFLIK - Purnawan Dwikora Negara (Widya Yuridika, 2018)
This shame culture is developed and maintained to serve as a means of traditional social control / social control so that the Tengger people always behave in accordance with Tengger norms and customs so as to avoid conflict. Culture of shame in Tengger society greatly influences its legal culture, that influence can be seen / manifested in never conflicts. The efforts of the Tengger people to maintain their shame culture through a social control system in the form of: (a) religious education; (b) Education in the Family by developing the paugeran-paugeran Tengger; (c) Advice, namely advice given by the elderly to the young or fellow, and; (d) Social suggestion, namely instilling the values of fun through folklore and legends around Tengger.Kata Kunci: Budaya Malu, Tengger, Budaya Hukum, Konflik